2010
DOI: 10.1111/j.1443-1661.2010.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Plastic Stents in the Treatment of Large Common Bile Duct Stones in 45 Patients

Abstract: Plastic biliary stenting may fragment common bile duct stones and decrease stone sizes. This is an effective and feasible method to clear large or difficult common bile duct stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 10 publications
(19 reference statements)
3
37
0
1
Order By: Relevance
“…For this reason, the use of longterm stenting should be limited to patients with a limited life expectancy. However, it has been reported that longterm stenting was effective in reducing the size of stones refractory to mechanical lithotripsy, and that complete elimination was achieved in 73.7-95.6% of cases when stone removal procedures were repeated after 3-6 months [135][136][137][138][139]. Even in patients given stents because stone removal had been difficult, complete stone removal may be achievable on retreatment; therefore reattempted stone removal is useful.…”
Section: Strength Of Recommendation (Agreement Rate): 2 (100%) Evidementioning
confidence: 99%
“…For this reason, the use of longterm stenting should be limited to patients with a limited life expectancy. However, it has been reported that longterm stenting was effective in reducing the size of stones refractory to mechanical lithotripsy, and that complete elimination was achieved in 73.7-95.6% of cases when stone removal procedures were repeated after 3-6 months [135][136][137][138][139]. Even in patients given stents because stone removal had been difficult, complete stone removal may be achievable on retreatment; therefore reattempted stone removal is useful.…”
Section: Strength Of Recommendation (Agreement Rate): 2 (100%) Evidementioning
confidence: 99%
“…In this study, we reported 86 % of the patients had successful stone removal after the second ERCP procedure. Among the factors that may contribute to this success is continuous friction between the stent and the stones caused by respiration and other biliary contractions, which facilitated of stone disintegration and reduced stone size [12]. Since increased friction may enhance this process, insertion of two stents was suggested to facilitate stone fragmentation [13].…”
Section: Discussionmentioning
confidence: 99%
“…57.5 % had a single bile duct stone, and the median diameter was 15 mm (7-30). The most commonly placed stents was 7 [5][6][7][8][9][10][11][12] cm in length and 10 [7][8][9][10] Fr in diameter. The median interval between the procedures was 2 (1-28) months (Table 1), and 90 % (n = 39) of the procedures were performed within 3 months.…”
Section: Characteristics Of the Patientsmentioning
confidence: 99%
“…However, the combination of EPLBD with limited EST provided spacious opening of the bile duct, reducing the need for mechanical lithotripsy (4.7% vs 7.9%, P < 0.05) in our study, which is consistent with previous reports [31] . For patients with difficult stones that are not suitable for extraction at the first attempt, the temporary placement of a stent might be an alternative method, and the plastic stents are able to fragment large CBD stones [35,36] . Pancreatitis is one of the most feared post-ERCP complications and occurs in 5%-19.8% of patients after EPBD [26] .…”
Section: Resultsmentioning
confidence: 99%